Extreme enhancement of secondary chirality through coordination-driven steric changes of terpyridyl ligand in glutamide-based molecular gels. Issue 50 (10th August 2020) - Takafuji, Makoto; Kawahara, Tomoki; Sultana, Nahid; Ryu, Naoya; Yoshida, Kyohei; Kuwahara, Yutaka; Oda, Reiko; Ihara, Hirotaka
Abstract : Dramatic changes of secondary chirality reflecting on enhancement of chiral signals ( i.e., CD and CPL) is induced through coordination-derived steric changes of terpyridyl ligand attached on glutamide-based molecular gels. Abstract : Aggregation-induced chirality is potentially useful in sensor technology applications. Herein we show extreme enhancement of secondary chirality through coordination-driven steric changes of terpyridyl ligand in molecular gels. The secondary chirality reflecting on enhancement of chiral signals ( i.e., circular dichroism (CD) and circularly polarised luminescence (CPL)) of the molecular gels formed from glutamide-attached terpyridine ( G -tpy ) is extremely enhanced by the coordination of its terpyridyl groups to metal ions such as Cu 2+, Zn 2+ and Ru 2+, which is due to dramatic changes in the stacked structure of the chromophore groups through the formation of metal ion complex. Metal-free terpyridine exists in a non-planar geometry, which suppress π–π stacking interactions among aggregates. The planarity of the terpyridyl group is improved through metal-ion complexation, which induces the metal-ion-coordinated terpyridyl groups to stack. The thermal stabilities of the CD signals are strongly affected by the metal-ion species. CPL signal is generated in the molecular gel formed from G -tpy –Zn 2+ complex accompanied by chelation-enhanced fluorescence. It is expected that large and sensitive coordination-driven secondary chirality signals (CD and CPL) are useful for sensing guest molecules and the surrounding environment.